Murine Models for Trypanosoma brucei gambiense disease progression--from silent to chronic infections and early brain tropism. - Christiane Giroud; Florence Ottones; Virginie Coustou; Denis Dacheux; Nicolas Biteau; Benjamin Miezan; Nick Van Reet; Mark Carrington; Felix Doua; Théo Baltz (Public Library of Science (PLoS), 2009)
Human African trypanosomiasis (HAT) caused by Trypanosoma brucei gambiense remains highly prevalent in west and central Africa and is lethal if left untreated. The major problem is that the disease often evolves toward chronic or asymptomatic forms with low and fluctuating parasitaemia producing apparently aparasitaemic serological suspects who remain untreated because of the toxicity of the chemotherapy. Whether the different types of infections are due to host or parasite factors has been difficult to address, since T. b. gambiense isolated from patients is often not infectious in rodents thus limiting the variety of isolates.T. b. gambiense parasites were outgrown directly from the cerebrospinal fluid of infected patients by in vitro culture and analyzed for their molecular polymorphisms. Experimental murine infections showed that these isolates could be clustered into three groups with different characteristics regarding their in vivo infection properties, immune response and capacity for brain invasion. The first isolate induced a classical chronic infection with a fluctuating blood parasitaemia, an invasion of the central nervous system (CNS), a trypanosome specific-antibody response and death of the animals within 6-8 months. The second group induced a sub-chronic infection resulting in a single wave of parasitaemia after infection, followed by a low parasitaemia with no parasites detected by microscope observations of blood but detected by PCR, and the presence of a specific antibody response. The third isolate induced a silent infection characterised by the absence of microscopically detectable parasites throughout, but infection was detectable by PCR during the whole course of infection. Additionally, specific antibodies were barely detectable when mice were infected with a low number of this group of parasites. In both sub-chronic and chronic infections, most of the mice survived more than one year without major clinical symptoms despite an early dissemination and growth of the parasites in different organs including the CNS, as demonstrated by bioluminescent imaging.Whereas trypanosome characterisation assigned all these isolates to the homogeneous Group I of T. b. gambiense, they clearly induce very different infections in mice thus mimicking the broad clinical diversity observed in HAT due to T. b. gambiense. Therefore, these murine models will be very useful for the understanding of different aspects of the physiopathology of HAT and for the development of new diagnostic tools and drugs.